The Chazar Forts of the Lower Don. Comparison (London Journal of Research In Humanities and Social Sciences, 2025)
The defense of the Khazar Khaganate fortresses has not been examined to date, although some assessments have been made of individual fortresses. It is difficult to compile a program for such a study. A typical assessment of an early medieval fortress includes: plan, building material, perimeter and area, walls with all their features; foundation/lack thereof; the presence/absence of towers, their number, metric characteristics of each, distances between them, moats, scarps, the structure of the fortress’s interior space, the presence of a citadel, a donjon, its location, height, the extent of the fortress’s development with residential and other structures, etc. The matter is complicated by the fact that not all of the aforementioned attributes have been established for Khazar fortresses due to their incomplete state of preservation and, especially, the insufficient amount of uncovered areas.